KONDISI LINGKUNGAN LEMBAGA PEMASYARAKATAN DAN DAMPAKNYA TERHADAP KELOMPOK RENTAN - Subroto, Mitro; Krisnandya, Genta Akbar (Ensiklopedia Sosial Review, 2024)
The conditions within correctional facilities significantly impact vulnerable groups, including women, children, and individuals with disabilities. This study aims to explore the environmental factors affecting these groups and the urgent need for improved policies. Utilizing a qualitative approach, the research analyzes existing literature and legal frameworks regarding prison conditions. The findings indicate that inadequate facilities, overcrowding, and lack of healthcare services exacerbate the vulnerabilities of these groups, leading to negative psychological and physical outcomes. The study concludes that reforming prison environments is essential to safeguard the rights and well-being of vulnerable populations within correctional institutions.